COVID-19 and mental health: A review of the existing literature - Rajkumar, Ravi Philip (Asian journal of psychiatry, 2020)
•Subsyndromal mental health concerns are a common response to the COVID-19 outbreak.•These responses affect both the general public and healthcare workers.•Depressive and anxiety symptoms have been reported in 16–28% of subjects screened.•Novel methods of consultation, such as online services, can be helpful for these patients.•There is a need for further long-term research in this area, especially from other countries The COVID-19 pandemic is a major health crisis affecting several nations, with over 720,000 cases and 33,000 confirmed deaths reported to date. Such widespread outbreaks are associated with adverse mental health consequences. Keeping this in mind, existing literature on the COVID-19 outbreak pertinent to mental health was retrieved via a literature search of the PubMed database. Published articles were classified according to their overall themes and summarized. Preliminary evidence suggests that symptoms of anxiety and depression (16–28%) and self-reported stress (8%) are common psychological reactions to the COVID-19 pandemic, and may be associated with disturbed sleep. A number of individual and structural variables moderate this risk. In planning services for such populations, both the needs of the concerned people and the necessary preventive guidelines must be taken into account. The available literature has emerged from only a few of the affected countries, and may not reflect the experience of persons living in other parts of the world. In conclusion, subsyndromal mental health problems are a common response to the COVID-19 pandemic. There is a need for more representative research from other affected countries, particularly in vulnerable populations.